A unilateral brachiocephalic vein thrombosis: cause of a rare, transient ischemic attack, a case report and review of the literature. (19th April 2013) - Liu, Guang Jian; Wang, Yun Fu; Liu, Zhi Gang; Liu, Jian Xin; Ding, Li; Zhang, Li Ping; Wang, Zheng Jun; Luo, Jie
<x xml:space="preserve">Abstract</x> The purpose of this report is to inform medical professionals of a case in which brachiocephalic vein thrombosis caused a transient ischemic attack (TIA). A brain computerized tomography (CT) scan, magnetic resonance imaging, digital subtraction angiography, head and lung CT angiography, jugular venography, cardiac color Doppler ultrasound scan, color Doppler ultrasound scan of the neck and lower vascular extremities and 24-hour, continuous electrocardiogram monitoring were performed. A 50-year-old male experienced a total of 31 onsets of weakness in the right side of his body, speech impairment and numbness in the right side of his body during a period of 20 days. Imaging results did not reveal evidence of a cerebral infarction. The potential of a TIA with an arterial origin and other causes were ruled out, and a left brachiocephalic vein thrombosis and left jugular vein congestion were discovered. Thus, the brachiocephalic vein thrombosis was considered to be the cause of the TIA. The patient received anticoagulant and antiplatelet aggregation treatment. On the following day after the termination of the TIA, a color Doppler ultrasound scan detected the opening of the jugular venous arch, but the blood flow that returned to the superior vena cava via the left brachiocephalic vein did not significantly increase. A brachiocephalic vein thrombosis can be the cause of a TIA. In addition to the anticoagulant and antiplatelet aggregation treatment, the opening of the collateral of veins, including that of the jugular venous arch, may play an important role in reducing venous congestion and in terminating TIAs.